2015
DOI: 10.1021/acs.jcim.5b00278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Wilma-SIE Virtual Screening Method in Community Structure–Activity Resource 2013 and 2014 Blind Challenges

Abstract: Prospective assessments of the Wilma-SIE (solvated interaction energy) platform for ligand docking and ranking were performed during the 2013 and 2014 editions of the Community Structure–Activity Resource (CSAR) blind challenge. Diverse targets like a steroid-binding protein, a serine protease (factor Xa), a tyrosine kinase (Syk), and a nucleotide methyltransferase (TrmD) were included. Pose selection was achieved with high precision; in all 24 tests Wilma-SIE top-ranked the native pose among carefully generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…For more information about the various methods, the reader is encouraged to read the manuscripts that the participants have submitted to this special issue. Their papers properly describe the unique features of their methods and what they have learned from the CSAR 2014 exercise. ,,,, …”
Section: Methodsmentioning
confidence: 99%
“…For more information about the various methods, the reader is encouraged to read the manuscripts that the participants have submitted to this special issue. Their papers properly describe the unique features of their methods and what they have learned from the CSAR 2014 exercise. ,,,, …”
Section: Methodsmentioning
confidence: 99%
“…22 ) Structural refinement was then carried out by energy minimization using the AMBER force field 39,40 with a distance-dependent dielectric (4r ij ) and infinite cutoff for nonbonded interactions, constraining the non-hydrogen atoms at their crystallographic positions with a harmonic force of 5 kcal mol −1 A −2 . Additional refinement was also applied for each sampling−scoring protocol described below.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…For example, Cui et al showed the advantage of SIE over MM/GBSA in calculating absolute G in the simulation of Ras-Raf and Ras-RalGDS [17]. Additionally, SIE approach has been ranked as one of the best scoring functions in several rounds of Community Structure-Activity Resource (CSAR) and Statistical Assessment of the Modeling of Proteins and Ligands (SAMPL) challenges [18][19][20][21]. However, the performance of SIE approach on achieving accurate G prediction is still far from perfect, which might be related to its usage of Amber force field that cannot tackle electrostatic polarization, an indispensable term for predicting G accurately [22][23][24][25][26].…”
mentioning
confidence: 99%